Answer:
Both expressions are equivalent to 78 when t = 6 ⇒ answer A
Explanation:
* To solve this problem substitute the value of t and then check
the answer
∵ The first expression is 2(7t - 3) ⇒ simplify it
# 2(7t) = 14t
# 2(3) = 6
∴ 2(7t - 3) = 14t - 6
- Substitute t by 4
∴ 14t - 6 = 14(4) - 6 = 56 - 6 = 50
- Substitute t by 6
∴ 14t - 6 = 14(6) - 6 = 84 - 6 = 78
∵ The second expression is 15t - 12
- Substitute t by 4
∴ 15t - 12 = 15(4) - 12 = 60 - 12 = 48
- Substitute t by 6
∴ 15t - 12 = 15(6) - 12 = 90 - 12 = 78
- The first expression has two values
# 50 when t = 4
# 78 when t = 6
- The second expression has two values
# 48 when t = 4
# 78 when t = 6
- From these information
# The two expressions have the same value 78 when t = 6
∴ Both expressions are equivalent to 78 when t = 6